Nilai Diri Disabilitas terhadap Dirinya Sendiri dalam Model Disabilitas - Imanuel Teguh Harisantoso (Jurnal Teologi Berita Hidup, 2023)
The study's objective is to explore the self-value of disability from a disability perspective. The model as an approach to disability studies has been categorically stigmatic. Looking at disability only at the model level, it falls into an understanding that tends to bring disability into categories, victims who deserve to be pitied (Charity model), the sick (medical model), not potential (social model), and stigmatized by negative identification by cultural models. The disability approach descriptively becomes an analytical knife to unravel the existence of disability problems, thus generating a new perspective on seeing disability. The study's results show that other new constructions of disability models that go beyond internal (self-medical) and external (socio-cultural) problems show that disability is not viewed from a negative perspective but from a different point of view. The relational model will bring disability in the I-Thou Buber relation and philosophically-theologically in the perichoresis relation. The relation is built on the principle of trinitarian relations: Father, Son, and Holly Spirit.